The ulcerectomy in the treatment of gastric ulcers, associated or not with vagotomy and drainage operation - Mañana, Julio; Guicheff, Vladimir; Pollak, Erik (Cirugía del Uruguay, 2020)
Eight cases of patients suffering from gastric ulcer are presented. They underwent resection of the ulcer to which was associated vagotomy with gastric drainage operation, as surgical treatment. This procedure was not adopted from choice, but became necessary· due either to the serious condition of the patients, to the location of the ulcerous crater, or the patients advanee age. Postoperatory evolution was good. W e believe this procedure is worth considerations for this type of patient.